Implementation of Prototyping Method in Developing a Web-Based Cos Management System using Laravel - Yudistio Izza Al Farisi (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2026)
This study develops a web-based boarding house management system using the Prototyping method to address administrative issues at Kos D'Rosse, where data was previously managed manually through Google Form, Excel, and WhatsApp. The Prototyping model enabled iterative requirements gathering and user evaluation to refine system features. The system was built using the Laravel framework with an MVC architecture and includes modules for tenant management, room monitoring, payment processing, financial reporting, and a real- time dashboard. Blackbox testing confirmed that all features functioned according to user needs, while whitebox testing produced low Cyclomatic Complexity values, indicating simple and maintainable program logic. User Acceptance Testing (UAT) showed improvements in operational efficiency, data accuracy, and decision-making speed. The results demonstrate that the system integrates all management activities into a single platform, reduces administrative workload, and provides accurate, real-time information. Overall, the Prototyping approach and Laravel MVC support structured development and effective system performance. Keywords: Laravel, Prototyping, Web-based System, Boarding House Management, MVC